2015
DOI: 10.1002/ajmg.a.36951
|View full text |Cite
|
Sign up to set email alerts
|

A de novo proximal 3q29 chromosome microduplication in a patient with oculo auriculo vertebral spectrum

Abstract: Oculo auriculo vertebral spectrum (OAVS; OMIM 164210) is a clinically and genetically heterogeneous disorder originating from an abnormal development of the first and second branchial arches. Main clinical characteristics include defects of the aural, oral, mandibular, and vertebral development. Anomalies of the cardiac, pulmonary, renal, skeletal, and central nervous systems have also been described. We report on a 25-year-old male showing a spectrum of clinical manifestations fitting the OAVS diagnosis: hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Moreover, a single case with the typical dup3q29 presented with isolated anophthalmia (20), enlarging the clinical heterogeneity associated with the duplication 3q29 syndrome. In another patient with hemifacial microsomia (OMIM %164210) the 0.7 Mb duplication also affected region 3q29, but located proximal to the typical region (22). An involvement of at least two genes in formation of the mental phenotype in dup(3q29) has repeatedly been discussed (17,18,21), as PAK2 and DLG1 map to the commonly affected region at 3q29.…”
Section: Duplication 3q29 (Dup3q29) Syndromementioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, a single case with the typical dup3q29 presented with isolated anophthalmia (20), enlarging the clinical heterogeneity associated with the duplication 3q29 syndrome. In another patient with hemifacial microsomia (OMIM %164210) the 0.7 Mb duplication also affected region 3q29, but located proximal to the typical region (22). An involvement of at least two genes in formation of the mental phenotype in dup(3q29) has repeatedly been discussed (17,18,21), as PAK2 and DLG1 map to the commonly affected region at 3q29.…”
Section: Duplication 3q29 (Dup3q29) Syndromementioning
confidence: 94%
“…The female reported by Rosenberg et al also showed a paternally inherited dup3q29, associated with MI, facial dysmorphism and ataxia. Subsequently, Lisi et al , defined the dup3q29 syndrome and at least 25 patients have been described yet . However, several patients showed overlapping or smaller duplications or a dup3q29, that only bordered the common deleted region and these were excluded in a phenotype review provided by Fernández‐Jaén et al .…”
Section: Phenotypic Features Of Patients With ‘Pure’ Duplication 3qmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3q29 microduplication syndrome (Online Mendelian Inheritance in Man 611936) is usually associated with an intellectual disability or global developmental delay, language delay, mild facial dysmorphisms, congenital heart diseases, skeletal malformations, eye anomalies, and obesity [1][2][3][4][5][6][7][8][9]. The genes that contribute to the clinical features of this syndrome are not clear, but the range of the copy number variation goes from 1.6 to 2.3 Mb, including the transferrin receptor (TFRC) and 3-hydroxybutyrate dehydrogenase 1 (BDH1) genes [9].…”
Section: Introductionmentioning
confidence: 99%